ACUTE AND SUB-CHRONIC TOXICITY ASSESSMENT OF PYRIDOSTIGMINE BROMIDE 90 MG EXTENDED- ELEASE TABLETS IN EXPERIMENTAL ANIMALS - Do Phong Tue; To Minh Hung; Le Quoc Hung; Nguyen Hai Duong; Nguyen Van Thinh; Vu Thi Que (Tạp chí Y học Quân sự, 2024)
Purpose: This study aimed to assess the acute and subchronic toxicity of Pyridostigmine bromide 90 mg extended-release tablets in experimental animals. Subjects and methods: Pyridostigmine bromide 90 mg extended-release tablets were prepared complying in-house specifications. Acute oral toxicity (LD50) was determined in white mice using the Litchfield-Wilcoxon method. Subchronic toxicity was assessed in rabbits following OECD guidelines. Results: The acute toxicity study revealed an LD50 of 17.9 mg/kg when Pyridostigmine bromide 90 mg extended-release tablets were orally administered to mice. In the subchronic toxicity assessment, rabbits were treated with Pyridostigmine bromide tablets for 28 days. Doses of 7.2 mg/kg/day and 21.6 mg/kg/day showed no significant alterations in hematological parameters (red blood cells, hemoglobin, hematocrit, mean corpuscular volume, white blood cells, platelets), blood biochemical parameters (AST, ALT, total protein, creatinine, urea), and did not cause damage to the histopathology of the liver, spleen, and kidneys in rabbits. However, the dose of 21.6 mg/kg/day resulted in a statistically significant difference in rabbit weight gain compared to those administered a dose of 7.2 mg/kg/day and those in the control group.